Factors affecting financial wellbeing of the university students. An empirical paper - Mohamad , Amri; Asat, Siti Haliza; Yusoff, Muhammad Saiful Anuar; Ashari, Anis Abul Hasan; Ishak, Rosbi; Wan Ali, Wan Roshaini; Hassan, Othman Zailani; Idris, Sufian (International Journal of Accounting, Finance and Business, 2025)
This is an empirical paper showing the linkages on the relationship between factors affecting the financial well-being of university students. The focus on the financial well-being of university students is very important to ensure that university students do not encounter financial difficulties during their years at universities. To be more specific, this paper examines the four factors which determine the financial well-being of university students which are Budget & Financial Education, Structured Funding, Unstructured Funding, and Financial Behaviour. The objectives of this research are to establish the extent of the conceptual relationship between four determining factors and the students’ financial well-being. The aims and objectives of this research are accomplished when the conceptualizations of each of the independent variable dimensions and students’ financial well-being are established and the linkages are clearly explained and empirically tested.